PERAN PENDIDIKAN AGAMA ISLAM SEBAGAI SOLUSI TERHADAP TANTANGAN MORAL DI DESA EMBONG SIDO - Hira Khoiriatul’Ulum; Deri Wanto; Hendra Harrmi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The background is that in society there are often bad moral problems that hit society, especially among adolescents and children. This moral crisis has caused moral and moral damage, there are many deviations here and there. Therefore, it is closely related to religious education, because religious education is very important in efforts to improve the progress of the nation and state. The purpose of this study was to determine the role of Islamic religious education as a solution to moral challenges in the village of Embong Sido. The type of research used in this qualitative research is Field Research. This study used a descriptive research approach, therefore no hypotheses were made during the research process. The data collection techniques for this research are observation, interviews, and documentation. From the research results, the role of religious education in Embong Sido Village in shaping the morale of children and youth in society is very important, to form good morals for their children, parents make several efforts, such as taking their children to recite the Koran at the mosque every evening, teaching children to be polite and respectful. to parents, and teach children to pray from an early age.